Toothache and tooth extraction as reasons for dental visits: an analysis of the 2019 National Health Survey - Amanda Ramos da Cunha; Lucelen Fontoura Bastos; Betine Pinto Moehlecke Iser; Deborah Carvalho Malta; Paulo Sávio Angeiras de Goes; Fernando Neves Hugo (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: The aim of this study was to analyze the prevalence of dental visits due to toothache and tooth extraction in Brazil and its association with individual and contextual variables. This two-step cross-sectional study included persons aged 18 years and older in the 2019 National Health Survey who had visited a dentist in the 12 months prior to the interview (n = 40,369). The individual-level outcome was having a dental visit due to toothache or tooth extraction. The ecological-level outcome was the proportion of dental visits for these reasons relative to all dental visits by Brazilian state. Associations with individual - sociodemographic characteristics, number of teeth, and type of health service used - and ecological variables - HDI and dental service coverage - were assessed using Poisson regressions. The prevalence of dental visits due to toothache or extraction was higher among individuals with no formal education, household income < 25% of the minimum wage, of black and brown skin color, living in rural areas, who consulted in the public health system, with 10-19 and 1-9 teeth, and men. The proportion of dental visits due to toothache/extraction in Brazilian states was negatively associated with the HDI and the rate of dental emergency team/100,000 inhabitants and positively associated with primary dental care coverage. The prevalence of dental visits due to toothache/extraction was associated with individual and ecological characteristics, indicating inequities in reasons for dental visits in Brazil. The potential of a well-structured oral health care network to overcome these inequities is suggested and needs to be better explored.